2014
DOI: 10.14685/rebrapa.v4i2.114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical Characteristics from Industrial and handcrafted Cachaça commercialized in the North Central Region from Paraná State

Abstract: <p>Cacha&ccedil;a is the second most consumed alcoholic beverage by Brazilians, only losing position for beer. Its manufacturing is divided into handcrafted (still) and industrial (distillation column). The objective of this study was to evaluate the quality of cacha&ccedil;a handcrafted and industrialized in the north central region of Paran&aacute; by physicochemical measurements of volatile acidity, alcohol content, pH, copper, higher alcohols, aldehydes, esters, furfural and methanol; as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(27 reference statements)
0
2
1
Order By: Relevance
“…The cachaças from the states of Maranhão and Paraná had a percentage of non-compliance with legal regulations regarding the content of esters, much higher than in this research, being 15 and 18%, respectively limit (Mendes et al, 2016;Duarte et al, 2017). Research has shown that the value of esters in cachaças obtained by column distillers had more than twice the ester content of cachaças distilled in stills, but it is not influenced by the burning of the cane or the storage barrel (Masson et al, 2007;Volpe et al, 2013).…”
Section: Physical-chemical Qualitycontrasting
confidence: 66%
See 2 more Smart Citations
“…The cachaças from the states of Maranhão and Paraná had a percentage of non-compliance with legal regulations regarding the content of esters, much higher than in this research, being 15 and 18%, respectively limit (Mendes et al, 2016;Duarte et al, 2017). Research has shown that the value of esters in cachaças obtained by column distillers had more than twice the ester content of cachaças distilled in stills, but it is not influenced by the burning of the cane or the storage barrel (Masson et al, 2007;Volpe et al, 2013).…”
Section: Physical-chemical Qualitycontrasting
confidence: 66%
“…This result is similar to that of Santiago et al (2015), which verified that 22.1 to 38.5% of 396 cachaças samples in Minas Gerais met limits established by legislation. The Volpe et al (2013) survey with cachaças from the northern region of the state of Paraná showed similar results, with 33.3% of the cachaça samples in disagreement with official parameters. As the limits determined by INMETRO for certification purposes were different from those established by the Ministry of Agriculture concerning the parameters volatile acidity (100 mg/100 mL anhydrous alcohol) and ethyl carbamate (150 μg/L), thirteen samples (65%) would not have had physical-chemical quality for INMETRO certification purposes.…”
Section: Physical-chemical Qualitymentioning
confidence: 59%
See 1 more Smart Citation